RODRIGO FACIO Y SU GENUINO PENSAMIENTO HUMANISTA EN LA UNIVERSIDAD - Cerdas Prado, Emmanuel (2018)
This essay consists in studying the humanistic thinking of Rodrigo Facio from the perspective of a student. In this syntetic essay it is explained his contributions to universitary life, the conception of education superior y as a statist in the constituent of 1949, which has marked the life of Costa Ricans. In conmemoration of his hundred years of born, the opportunity is given to a student, in a literary contest, of deepen into his humanism to defined from our recent times his actions for universitary model. The university system needs to have as a reference for young people, figures like Rodrigo Facio, promoting the academic transmission of a participating youth and interested in the reality of the country.